The Schorsing in Implementation of Administrative Decision that Endanger the Environment by Administrative Court - Miftah Sa'ad Caniago (Nagari Law Review, 2018)
The postponement criteria of the implementation of KTUN (Administrative Court Decision) based on Article 67 of the Act Number 5, 1986 concerning the State Administrative Court (the Act of Administrative Court) merely states that such Postponement can be made if there is a very urgent circumstance which results in the plaintiff's interest to be lost if the sued state’s administrative decision is still implemented. By the promulgation of the Act Number 30, 2014 on the Governance Administration, it reregulates the delay of the implementation of the decision worded in Article 65. However, there are varies in the regulation of the implementation of the such decision pursuant to Article 67, of the Act Law Number 5, 1986 concerning the State Administrative Court. In accordance with Article 65 of the Administrative Governance Act, it rules more detailed regarding the reasons for the State Administrative Court that may delay the enforcement of a Government Decree, one of which if a Government Decision or Action "has the potential to cause environmental damage" and the Court in issuing such a delay shall be in the form of a "Verdict", so that it is different from the arrangement in Article 67 of the State Administrative Judicature Law and its derivatives which stipulates that the reason for the postponement of the validity of a State Administrative Decree if there is an "urgent circumstance" issued in the form of "Stipulation". The research shows that the Act Number 30, 2014 as a substantive law does not regulate in detailed regarding procedural law of such adjournment application, hence based on the principle of lex specialis derogat legi generali a judge has to refer to the rule on the postponement that already exist till it is enacted the new one that might accommodate the postponement implementation and it can determine that the Postponement Execution Delay a judge must view the urgency of the Decision/the Government Action might be delayed by referring to review result or auditing from auditors of the environment that has been certified by the LSK of environmental auditors that is under the Ministry of Environment, and it is not against “ the public interest”.